Corporate Social Responsibility and Firm Performance among Malaysian Firms - Chan, Samantha; Fong Yew Ong (Journal of Technology Management and Business, 2022)
With the rise in corporate social responsibility (CSR) initiatives and greater awareness of sustainable development, CSR is rapidly evolving and firms’ involvement is increasing. However, the enforcement of mandatory disclosure does not necessarily mean firms will respond and go beyond these legislations. Thus, the underlying premise of positive financial outcomes could encourage firms to act beyond legislative compliance. This study first examined the current nature and extent of a firm’s CSR disclosure (CSRD), as measured by CSR dimensions workplace, marketplace, community, and environment. CSRD was measured through content analysis, through annual reports of 97 manufacturing firms in Malaysia from 2017 to 2019. A CSR disclosure index was adopted for this study. This study also determined the impact of CSRD on corporate financial performance (CFP) and identified which CSRD dimension had the greatest impact on CFP. Firm size, measured by the level of assets, sales, and market capitalisation, as well as earnings per share, were the control variables for this study. Data were analysed using Pearson’s correlation and multiple regression analysis. It was found that CSRD levels in manufacturing firms in Malaysia were still low and there was a mixed relationship between CSRD and CFP. The findings suggest that the relationship between CSR and CFP may be curvilinear. It was also found that community, workplace, and marketplace-related responsibility activities affected ROA the most, whereas the marketplace affected Tobin’s Q the most.